Return to climbing after musculoskeletal injury: a scoping review protocol of rehabilitation content, outcome measures and return to sport criteria in climbers - Ehiogu, U.; Wells, G.; Jones, G.; Buckthorpe, M.; Patterson, S. (BMJ Open Sport & Exercise Medicine, 2026)
Climbing is an Olympic sport featuring three disciplines: lead climbing, speed climbing and bouldering. The injury burden associated with climbing has been well documented. However, the content of rehabilitation programmes, the outcome measures and the return-to-sport (RTS) criteria after injury are sparse. This review will map the content of rehabilitation programmes, examine outcome measures to inform rehabilitation and RTS using a COSMIN-aligned approach, and identify objective and subjective criteria used for return to climbing after musculoskeletal injury (MSKI). The methodological framework of Arksey and O`Malley will be applied for this scoping review. A systematic review of four online databases and a manual search of reference lists of identified articles will be used to identify relevant papers. Given the limited empirical literature on this topic, both peer-reviewed and non-peer-reviewed sources written in English will be used. Sources reporting rehabilitation, recovery, outcome measures in injured and uninjured climbers and RTS/return to climbing criteria after MSKI will be included. All climbers (elite, professional and/or recreational) of any age and sex will be included. Statistical analysis of agreement between reviewers at each stage of the review will be undertaken. This review will inform future research on the rehabilitation content after MSKI. It will also aid in designing sports-specific testing batteries and in return-to-climbing decision-making criteria. The result of this review will be relevant to clinicians, performance staff and researchers and will be disseminated through publications and presentations.